Place of open thoracostomy in the treatment of chronic pleural empyema - Brandolino, Mario; Bertullo, Hugo; Nin Vivo, Jorge; Pomi, Jorge (Cirugía del Uruguay, 1985)
Chronic pleural empyema continues to be a serious sanitary problem due to the complex therapeutic solutions implicated. 41 patients are presented, 15 of them submitted to a temporary open thoracostomy. In 9 cases a surgical closure was done, in 6 closure was spontaneous. In 26 cases open thoracostomy was a definiti· ve solution.